Idiopathic Clubbing Confined to Lower Limb Digits and Idiopathic Pulmonary Fibrosis: An Unusual Association. (22nd October 2012) - Magazine, Rahul; Shetty, Ranjan; Goneppanavar, Umesh; Mohapatra, Aswini K.
Abstract : A 62-year-old housewife presented to the chest outpatient department with a history of exertional breathlessness of four-month duration. On general physical examination, clubbing of toes was present with sparing of fingers. Chest examination revealed bilateral basal end inspiratory fine crepitations. A diagnosis of idiopathic pulmonary fibrosis was made on the basis of clinical, spirometric, and high-resolution computed tomography findings. Extensive evaluation could not reveal any cause for the differential clubbing. The unusual distribution of clubbing in a clinical condition, such as idiopathic pulmonary fibrosis, where generalized clubbing is expected can lead to a diagnostic confusion. This can lead to a further burden of investigations on the patient as clubbing being a significant finding cannot be ignored.